2006
DOI: 10.1007/s00508-006-0552-y
|View full text |Cite
|
Sign up to set email alerts
|

Does endoscopic ultrasound staging already allow individual treatment regimens in gastric cancer

Abstract: According to our results the accuracy of EUS staging matched pathohistological staging with regard to tumor infiltration and lymph node stage in 68% and 57% of cases respectively. Underestimation of the final T2 and T3 stages as T1 stage by EUS presents a problem regarding the consistency of EUS examination at our institution, particularly with respect to individual treatment for early gastric cancer. The present uncertainty in EUS stage reliability makes it necessary to have a strategy of radical resection wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…Only one AUS study had a prospective study design [53], in only one EUS study the time interval between EUS and the reference test was less than 16 days [29], and in none of the FDG-PET(/CT fusion) studies the time interval between FDG-PET(/CT fusion) and the reference test was less than 16 days. Except for one AUS study [23], one EUS study [29], and one FDG-PET study [30], none of the included studies applied histopathological analysis after ≥D2 lymphadenectomy in all patients. Furthermore, the quality of pathological examinations of excised LNs, the skills of the surgeons, and the tumor extensions may also have affected sensitivity and specifi city.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one AUS study had a prospective study design [53], in only one EUS study the time interval between EUS and the reference test was less than 16 days [29], and in none of the FDG-PET(/CT fusion) studies the time interval between FDG-PET(/CT fusion) and the reference test was less than 16 days. Except for one AUS study [23], one EUS study [29], and one FDG-PET study [30], none of the included studies applied histopathological analysis after ≥D2 lymphadenectomy in all patients. Furthermore, the quality of pathological examinations of excised LNs, the skills of the surgeons, and the tumor extensions may also have affected sensitivity and specifi city.…”
Section: Discussionmentioning
confidence: 99%
“…• The sensitivity and specifi city of AUS for the detection of LN metastasis varied between 12.2% and [33] 2004 − − − − − + − + + + − − − 2 2 31 Lee et al [42] 2001 − − − + + + − + + + + + + 4 5 69 Düx et al [53] 1997 + − + + − + − + + − + + + 5 4 69 Kim et al [54] 1997 − − + − + + − − + + − + + 3 4 54 Stell et al [57] 1996 − − − − + − − + + + + + + 2 5 54 EUS Lok et al [17] 2008 − − − − + − − − + + + − + 1 4 38 Bentrem et al [19] 2007 + − − + + + − + + − + + + 5 4 69 Tan et al [20] 2007 − − + + + + − + + + − − − 5 2 54 Arocena et al [24] 2006 + − − − + + − − + + − + + 3 4 54 Ganpathi et al [25] 2006 − − − − + + − + + + + − + 3 4 54 Tsendsuren et al [26] 2006 − − − + + + − + + + − − − 4 2 46 Ang et al [27] 2006 + − − − + + − − + − − + − 3 2 38 Potrc et al [29] 2006 + + − + + + − + + − − + + 6 3 69 Polkowski et al [34] 2004 + − − − + + − + + + + + + 4 5 69 Bhandari et al [35] 2004 + − − − + + − + + + − − + 4 3 54 Javaid et al [36] 2004 − − − + + + − + + + − + − 4 3 54 Habermann et al [37] 2004 + − − + + + − + + + + − + 5 4 69 Xi et al [40] 2003 − − − + + + − + + + − + − 4 3 54 Chen et al [41] 2002 − − + + + + − + + + + + + 5 5 77 Willis et al [43] 2000 + − − + + + − + + + + + − 5 4 69 Tseng et al [44] 2000 − − − + + + − + + + − + + 4 4 62 Mancino et al [46] 2000 − − − + + + − + + + − − − 4 2 46 Akahoshi et al [48] 1998 + − − − + + − + + + + + − 4 4 62 Hunerbein et al [49] 1998 + − − − + + − + + − − − + 4 2 46 Wang et al [50] 1998 + − − + + + − + + + − + − 5 3 62 Hamada et al [52] 1997 − − − + + + − + + + − − − 4 2 46 Hunerbein et al [55] 1996 + − − − − + − + + − + + − 3 3 46 François et al [56] 1996 + − − − + + − + + + − + − 4 3 54 Perng et al [58] 1996 + − − + + − − − + + − + − 3 3 46 Smith et al [60] 1993 − − − + + + − + + − − − + 4 2 46 Ziegler et al [61] 1993...…”
Section: Staging Performanceunclassified
“…A US intraoperatória da peça cirúrgica ressecada, por outro lado, atinge 93,5% de concordância com os achados histopatológicos (23) . Na avaliação da categoria T, nesta casuística, a EE concordou em 83,3% dos casos com a histopatologia e/ou cirurgia, concordante com os dados de literatura, variáveis de 71% a 92% (1,16,29,41,47,48) . Avaliou-se para cada subdivisão desta categoria a sensibilidade, a especificidade, o valor preditivo positivo, o valor preditivo negativo e a exatidão, uma vez que se estudavam apenas casos confirmados pela histopatologia e/ou cirurgia.…”
Section: Discussionunclassified
“…Para os casos T1 e T2, os índices de concordância desses exames com os achados histopatológicos são baixos. Nesse campo, a ecoendoscopia (EE) vem sendo utilizada em vários países, com alta precisão na classificação da categoria T (3,16,41) . O objetivo deste trabalho foi avaliar os dados obtidos pela EE na determinação pré-operatória do estádio da doença em doentes com adenocarcinoma do estômago, verificando sua correlação com os achados cirúrgicos e/ou histopatológicos.…”
Section: Introductionunclassified
“…We identified 29 studies, with 2500 patients, that reported on the accuracy of EUS staging for gastric cancer between 1988 and 2009; 37-65 21 [37][38][39][40][41][43][44][45]47,48,[50][51][52][53]56,57,59,[62][63][64][65] used radial ultrasound probes, three 49,58,60 used linear array probes and five 42,46,54,55,61 did not report the type of probe ( Table 1). As the reported accuracy of linear array probes for both T and N stages did not differ from that of the rest, we include them here.…”
Section: Gastric Cancersmentioning
confidence: 99%